Contrasting geochemical signatures of Devonian and Permian granitoids from the Tseel Terrane, SW Mongolia - Burenjargal,U.; Okamoto,A.; Tsuchiya,N.; Uno,M.; Horie,K.; Hokada,T. (Journal of Geosciences, 2016)
The Tseel Terrane in SW Mongolia contains abundant Devonian and Permian granitoid intrusions that formed during the evolution of the Central Asian Orogenic Belt (CAOB). The newly obtained SHRIMP zircon ages for three granitoids in the central part of the Tseel are all Permian, 281.3 ± 1.1 Ma, 279.1 ± 0.8 Ma and 278.0 ± 1.6 Ma (2σ). On the La/Gd vs. La diagram the granitoids are classified into two groups, whereby Group 1 has higher La concentrations and La/Gd ratios than Group 2. Although the number of dated samples is limited, Devonian and Permian ages are assumed for the Group 1 and 2, respectively. Group 1 shows enrichment in Large Ion Lithophile Elements, as well as negative anomalies for High Field Strength Elements such as Nb, Hf, and Zr in Primitive mantle-normalized spiderplots. This may indicate a contribution of slab-derived fluids to melting or anatexis of upper continental crust. The Group 2 is poorer in Ba, Eu, Sr, Ti and LREE indicating fractionation of feldspar, ± Bt with Mnz and opaque mineral(s). These findings, combined with the results of previous petrological and chronological studies, suggest that the Devonian granitoids were generated by relatively deep melting, within garnet stability field; they were emplaced at mid-crustal levels, during regional high-T and low-P metamorphism. On the other hand, the Permian intrusions solidified from a highly fractionated melt, probably in a relatively shallow crust.
Keywords: granitoids; geochemical characteristics; Tseel Terrane; SW Mongolia